Teacher Self-Efficacy: The Missing Piece to Trauma-Informed Classroom Interventions - Sarah Lancaster (The Advocate, 2021)
Once a child enters kindergarten they spend the majority of their waking hours in school. Therefore, school-based interventions that are trauma informed are crucial for promoting social-emotional learning and development. While there are some promising studies, professional development programs for educators have not systematically incorporated psychoeducation on childhood trauma and the impact it has on behavior and learning, or classroom-based strategies to enhance learning and development among children with a trauma history (McConnico, Boynton-Jarrett, Bailey, & Nandi, 2016). Furthermore, educators’ perceptions on how comfortable they are dealing with the trauma of students has not been widely explored (Crosby, Day, Baroni, & Somers, 2015).
Keywords: Education; Teacher Self-Efficacy; Trauma-Informed Practices